Mobile Devices for Tertiary Study – Philosophy Meets Pragmatics for Remote Aboriginal and Torres Strait Islander Women - Townsend, Philip (The Australian Journal of Indigenous Education, 2015)
This paper outlines PhD research which suggests mobile learning fits the cultural philosophies and roles of Aboriginal and Torres Strait Islander women who are preservice teachers in the very remote Australian communities where the research was conducted. The problem which the research addresses is the low completion rates for two community-based Initial Teacher Education (ITE) programs in South Australia (SA) and Queensland (Qld). Over the past decade, the national completion rate of Aboriginal and Torres Strait Islander students in teacher training was 36 per cent, and in these two community-based programs it was less than 15 per cent. This paper identifies the perceptions of the benefits of using mobile devices by Aboriginal and Torres Strait Islander women who are preservice teachers in very remote communities. They report ways in which mobile learning supports their complex roles and provides pragmatic positive outcomes for their tertiary study in remote locations. The paper describes the apparent alignment between mobile learning and cosmology, ontology, epistemology and axiology, which may underpin both the popularity of mobile devices and the affordances of mobile learning.